Неореалізм: до проблеми термінологічного окреслення / Оксана Головій - Головій, Оксана Миколаївна (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглянуто неореалізм як перехідне / межове / «відкрито-закрите» (У. Еко) художнє явище; як ґрунтовану на новітніх філософських концепціях модерну (з 1980-х рр. – постмодерну) стильову тенденцію, котра засвідчила вияв у літературі ХХ ст. реалістичного типу творчості і спирається на притаманну реалістичній естетиці здатність органічно поєднуватися з поетикально-стильовими елементами модернізму та постмо¬дер¬нізму. In the article neo-realism as transitional / synthesized / «opened-closed» (by Y. Eko) phenomenon is analyzed; as a modernist (since 1980 – post-modernist) stylistic trend, which testified to the manifestation of a realistic kind of creative work in modern art. It is based on the ability peculiar to realistic aesthetics to make links with modernism and post-modernism. Differences between poetically-stylistic descriptions of classic realism of 19th centuries and neo-realism are linked with changes of the arts paradigms, philosophic and aesthetic doctrines. Realism of 19th centuries was formed on the base of materialistic-positivist philosophy, neo-realism was formed on the base of philosophy 20th century. Philosophy of life became the base of modernistic neo-realism, existentialism and post-structuralism conceptions became the base of post-modernistic neo-realism. We must to allot based phases of evolution of neo-realism: 1) 1900–1920, 2) «Soviet period» (1920–1930; 1930–1940; 1950–1980), 3) the end of 1980–2000.
Keywords: реалізм; неореалізм; модернізм; постмодернізм; "філософія життя"; екзистенціалізм; тип творчості; стильова тенденція